2016
DOI: 10.3233/jad-150811
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Memory Decline: Two Population-Based Prospective Studies

Abstract: Background Vitamin D deficiency has been linked with dementia risk, cognitive decline and executive dysfunction. However, the association with memory remains largely unknown. Objective To investigate whether low serum 25-hydroxyvitamin D (25(OH)D) concentrations are associated with memory decline. Methods We used data on 1,291 participants from the US Cardiovascular Health Study (CHS) and 915 participants from the Dutch Longitudinal Aging Study Amsterdam (LASA) who were dementia-free at baseline, had valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 40 publications
1
39
0
Order By: Relevance
“…In the ARIC (Atherosclerosis Risk in Communities) Study [35], lower levels of 25OHD were not significantly associated with lower cognitive test scores at baseline or with greater decline in cognitive test scores over 3 and 11-year follow-ups. Prospective studies of memory have also had variable results; low VitD was associated with visual memory decline in the Cardiovascular Health Study (CHS), but not with verbal memory change in the Longitudinal Aging Study Amsterdam (LASA) [36]. It is notable that our study, like most other prospective studies of VitD and cognitive function, is based on a single baseline measurement of VitD.…”
Section: Discussionmentioning
confidence: 94%
“…In the ARIC (Atherosclerosis Risk in Communities) Study [35], lower levels of 25OHD were not significantly associated with lower cognitive test scores at baseline or with greater decline in cognitive test scores over 3 and 11-year follow-ups. Prospective studies of memory have also had variable results; low VitD was associated with visual memory decline in the Cardiovascular Health Study (CHS), but not with verbal memory change in the Longitudinal Aging Study Amsterdam (LASA) [36]. It is notable that our study, like most other prospective studies of VitD and cognitive function, is based on a single baseline measurement of VitD.…”
Section: Discussionmentioning
confidence: 94%
“…5,7,8,16,27,[36][37][38][39][40][41] Eight studies reported vitamin D as a continuous variable, 5,6,10,27,29,36,39,42 27 as a categorical variable, and three reported both. Seventeen studies used a-priori cut offs 6,8,[14][15][16]28,34,35,37,41,[43][44][45][46][47][48][49] and 13 categorized into tertiles, 9,17,38,50,51 quartiles, 7,12,18,33 or quintiles. 13,40,52,53 The majority of studies analyzed serum 25OHD with four analyzing plasma 25OHD.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Ten studies classified cognition dichotomously (e.g. decline vs no decline) 9,11,12,17,18,33,43,45,51,53 and 28 reported cognition as a continuous score. Overall, 52 neuropsychological tests were used (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 The Lawton IADL scale 22 These include thyroid dysfunction, vitamin B12 deficiency, and depression. More recently, there is evidence for underlying sleep disorders, 31 sensorineural hearing loss, 32 and vitamin D deficiency 33 as potential treatable contributors to cognitive impairment. Harnessing brief screens such as the STOP-BANG Sleep Apnea questionnaire, 34 Hearing Handicap Inventory for the Elderly Screening Version, 35 and the brief Geriatric Depression Scale 36 may help in screening for these causes.…”
Section: Screening For Cognitive Impairment: Tools and Approachesmentioning
confidence: 99%